2003
DOI: 10.1159/000071837
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Prostate Cancer and Changes in Prostate-Specific Antigen (PSA) Six Months after Surgery for Benign Prostatic Hyperplasia in Patients with Elevated PSA

Abstract: Objective: To evaluate early postoperative results of patients with elevated prostate-specific antigen (PSA) levels who underwent surgery due to benign prostatic hyperplasia (BPH). Patients and Methods: 64 patients who had lower urinary tract symptoms (LUTS), normal digital rectal examinations (DRE), elevated PSA levels and prostate biopsies reported as being benign pathologically in specimens obtained by transrectal ultrasound (TRUS)-guided biopsies, were included in the study. Patients were assessed in accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
(19 reference statements)
4
6
0
Order By: Relevance
“…This is comparable with the results (11%) reported by Boddy et al It is interesting that the PSA rise in the first 6 months after operation was generally induced by the inflammatory process: carcinoma was found in only 1 of 6 patients who underwent biopsies during this period. These data are very similar to those reported by Ozden et al [23]. It must be also emphasized that 37% of our patients were actively requested to come back for follow-up visits.…”
Section: Discussionsupporting
confidence: 92%
“…This is comparable with the results (11%) reported by Boddy et al It is interesting that the PSA rise in the first 6 months after operation was generally induced by the inflammatory process: carcinoma was found in only 1 of 6 patients who underwent biopsies during this period. These data are very similar to those reported by Ozden et al [23]. It must be also emphasized that 37% of our patients were actively requested to come back for follow-up visits.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with our experience with an 85.5% reduction in PSA with a mean tissue weight of 118 G in our combined HoLEP and upper tract stone procedure cohort. PSA reductions of 85.5% to 91.7% for HoLEP [16,36] compare favorably with decreases of 71.3% to 95.6% for open prostatectomy [45][46][47] and of 69.7% to 83.5% for TURP [45][46][47][48]. These large decreases in PSA objectively corroborate our impression that HoLEP provides a thorough resection of prostatic tissue and that the amount of reduction in PSA appears to be an excellent surrogate measurement of adenomatous tissue removal.…”
Section: Resultssupporting
confidence: 75%
“…HoLEP offers significant advantages over TURP and open prostatectomy and should be considered as primary therapy for every patient requiring surgical therapy for BPH. [36] HoLEP (10) 85.5 6.2 0.9 118 6 Ozden et al [47] Open/TURP (32) 74.2 14.8 3.7 N/A 6 Marks et al [45] Open/TURP (82) 71.3 4.6 0.7 35 6 Aus et al [48] TURP (190) 69.7 6 1.9 33.5 3 Stamey et al [46] Open (7) 95. 6 24.1 1 88.9 N/A Stamey et al [46] TURP (73) 83.5 7.9 1.3 29 N/A Hai and Malek [49] KTP (10) 42.4 3.3 1.9 11.1 12 BPH-benign prostatic hyperplasia; HoLEP-holmium laser enucleation of the prostate; KTP-potassium titanyl phosphate; PSA-prostate-specific antigen; TURP-transurethral resection of the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate volume and symptomatic prostatic inflammation are the two most important factors contributing to the elevated PSA levels in men without clinically detectable PC [13]. Recently, studies have shown that asymptomatic prostatitis can elevate the PSA significantly [14][15][16][17]. In this study, the relationship between asymptomatic prostate inflammation and PSA elevation was not assessed.…”
Section: Discussionmentioning
confidence: 88%